Role of colposcopy in the diagnosis of malignant lesions of the uterine cervix - Baca Mazur, Jorge (2015)
OBJECTIVES: To demonstrate the importance of using colposcopy in diagnosis of cervical cancer. MATERIAL AND METHODS: A retrospective, observational and descriptive study, between January 2001 and December 2004, in the colposcopy clinic, Regional Hospital "Eleazar Guzman Barron" Chimbote, Peru. RESULTS: 513 colposcopy performed, 78 Biopsy studies were made, with the following results: 18 invasive squamous cell carcinomas, 16 squamous intraepithelial lesions (SIL) high grade, low-grade SIL August 7 squamous metaplasia, 25 cases of chronic cervicitis, 6 benign polyps and one adenocarcinoma. CONCLUSION: the value of colposcopy as a diagnostic method of premalignant and malignant cervical pathology arises.